A Comparative Study of Local and Global Construction Materials Sourcing Strategies for Road Projects in Nigeria - Ajiboye, Araoye Olarinkoye; Silas, Micaiah Zhitsu; Adindu, Chinedu Chimdi; Alhassan, Elijah Aina; Kolo, Stephen Sunday (UI Scholars Hub, 2024)
This study is a comparative analysis of local and global sourcing strategies to determine the impact of strategic material sourcing on road construction project performance. The study aimed to evaluate the effects of material-sourcing strategies on the performance of road construction companies in Nigeria. A mixed-methods approach was used, incorporating both qualitative and quantitative research. Data collection involved sampling techniques using structured questionnaires and oral interviews. Regression analysis evaluated the relationship between strategic material sourcing and road construction performance. The results revealed that 87.5% of the materials used by road construction companies in the study areas were sourced from the local market, which indicates a high dependence on local resources and substantial investments and purchases within the local economy. Additionally, it was shown that local material sourcing was advantageous over global sourcing in terms of quick delivery and cost savings on road projects. However, the study also revealed that global material sourcing was necessary for projects requiring advanced and higher-quality materials. The study concludes that a high percentage of domestic material sourcing is essential for boosting the Nigerian economy through industrialization, employment generation, and a robust and self-sufficient economy. It is recommended that both government and private material suppliers explore ways to enhance the quality and availability of local road construction materials through advanced manufacturing technologies to improve service delivery by road project contractors. Furthermore, expanding the existing road material procurement process could create opportunities for construction companies beyond the local area and foster healthier competition among them by leveraging economies of scale.